Engaging Community College FacultyThe Benefit of Learning Communities - Deanne Grier Yates (Adult Education Research Conference, 2015)
Community college faculty engagement encouraged by the creation and support of learning communities will be explored. The focus will be on current literature outlining the unique challenges facing community college faculty and the creation and application of learning communities in the community college setting.
Keywords: community college faculty engagement; community college faculty involvement; community college faculty satisfaction; learning communities; faculty professional development.